Attitudes of parents toward their children with speech disorders in Oyo State, Nigeria (2015)
Good speech is essential to both social and academic lives. However, when speech loss its quality, it attracts unnecessary reaction from the listeners which may eventually cause psychological trauma to the affected person. Reaction to speech disorders vary from place to place and culture to culture and this has been the major concern of special educators and speech specialists. It is on this note that this study investigates attitudes of parents towards their children with speech disorders in Oyo State, Nigeria. The study employed survey research design. A total number of fifty (50) parents whose children have significant speech disorders were purposefully selected. A questionnaire tagged Parent Attitudinal Scale for Special Disorders with reliability coefficient of 0.71 was used for data collection. The findings revealed that parent’s dispositions to speech disorders were negative as there was no significant difference between the attitudes of male and female parents toward speech disorders of their children. However, there was significant different between the reaction of elite and illustrates parents towards speech disorder. Based on these finding, it was recommended that there should be mass awareness about the implication of negative reaction and proper education about early intervention to stem the tide.